WWOX-related encephalopathies: delineation of the phenotypical spectrum and emerging genotype-phenotype correlation. Issue 1 (19th November 2014) - Mignot, Cyril; Lambert, Laetitia; Pasquier, Laurent; Bienvenu, Thierry; Delahaye-Duriez, Andrée; Keren, Boris; Lefranc, Jérémie; Saunier, Aline; Allou, Lila; Roth, Virginie; Valduga, Mylène; Moustaïne, Aissa; et al.
Abstract : Background: Homozygous mutations in WWOX were reported in eight individuals of two families with autosomal recessive spinocerebellar ataxia type 12 and in two siblings with infantile epileptic encephalopathy (IEE), including one who deceased prior to DNA sampling. Methods: By combining array comparative genomic hybridisation, targeted Sanger sequencing and next generation sequencing, we identified five further patients from four families with IEE due to biallelic alterations of WWOX . Results: We identified eight deleterious WWOX alleles consisting in four deletions, a four base-pair frameshifting deletion, one missense and two nonsense mutations. Genotype-phenotype correlation emerges from the seven reported families. The phenotype in four patients carrying two predicted null alleles was characterised by (1) little if any psychomotor acquisitions, poor spontaneous motility and absent eye contact from birth, (2) pharmacoresistant epilepsy starting in the 1st weeks of life, (3) possible retinal degeneration, acquired microcephaly and premature death. This contrasted with the less severe autosomal recessive spinocerebellar ataxia type 12 phenotype due to hypomorphic alleles. In line with this correlation, the phenotype in two siblings carrying a null allele and a missense mutation was intermediate. Conclusions: Our results obtained by a combination of different molecular techniques undoubtedly incriminate WWOX as a gene for recessive IEE and illustrate the usefulness of high throughput data mining for the identification of genes for rare autosomal recessive disorders. The structure of the WWOX locus encompassing the FRA16D fragile site might explain why constitutive deletions are recurrently reported in genetic databases, suggesting that WWOX -related encephalopathies, although likely rare, may not be exceptional.